Role of TRAV locus in low caries experience - Briseño Ruiz, Jessica (2013)
Caries is the most common chronic, multifactorial disease in the world today; and little is still known about the genetic factors influencing susceptibility. Our previous genome-wide linkage scan has identified five loci related to caries susceptibility: 5q13.3, 13q31.1, 14q11.2, 14q 24.3, and Xq27. In the present study, we fine mapped the 14q11.2 locus to identify genetic contributors to caries susceptibility. Four hundred seventy-seven subjects from 72 pedigrees with similar cultural and behavioral habits and limited access to dental care living in the Philippines were studied. An additional 387 DNA samples from unrelated individuals were used to determine allele frequencies. For replication purposes, a total of 1,446 independent subjects from four different populations were analyzed based on their caries experience (low versus high). Forty-eight markers in 14q11.2 were genotyped using TaqMan chemistry. Transmission disequilibrium test was used to detect over transmission of alleles in the Filipino families, and Chi-square, Fisher’s exact and logistic regression were used to test for association between low caries experience and variant alleles in the replication data sets. We finally assessed the mRNA expression of TRAV4 in the saliva of 143 study subjects. In the Filipino families, statistically significant associations were found between low caries experience and markers in TRAV4. We were able to replicate these results in the populations studied that were characteristically from underserved areas. Direct sequencing of 22 subjects carrying the associated alleles detects one missense mutation (Y30R) that is predicted to be probably damaging. Finally, we observed higher expression in children and teenagers with low caries experience, correlating with specific alleles in TRAV4. Our results suggest that TRAV4 may have a role in protecting against caries.